The illustrations from the works of Andreas Vesalius of Brussels : with annotations and translations, a discussion of the plates and their background, authorship and influence, and a biographical sketch of Vesalius - Vesalius, Andreas, 1514-1564; O'Malley, Charles Donald, 1907-1970; Saunders, John Bertrand de Cusance Morant, 1903-1991 (New York : Dover Publications, 1973)
The definitive edition of the great Vesalius plates on human anatomy. Everything identified. 96 plates.
"The anatomical illustrations ... have been reproduced ... from Andreae Vesalii Bruxellensis Icones anatomicae, published in 1934."
Reprint of the ed. published by World Pub. Co., Cleveland.
Keywords: Human anatomy -- Atlases; Human anatomy -- Early works to 1800.